POTENSI ANTIBAKTERIAL EKSTRAK CACING TANAH LUMBRICUS RUBELLUS, PHERETIMA POSTHUMA DAN MEGASCOLEX SP. SEBAGAI OBAT ALTERNATIF - Suprihatin, Suprihatin; Noverita, Noverita (E-Journal Widya Kesehatan dan Lingkungan, 2005)
Being a tropical country Indonesia has vast biological resources but has not been explored maximally. Study on biological resource potential of plant as the raw materials of drugs has not been extensively done on animal biological resources. The study objective was to explore the medical potency of resources of an animal easily found in Indonesia such as worms. It is abundantly found living in tropical countries like Indonesia, cultivated with some organic compost media, and it is used as decomposer of garbage. Worm extract is believed to have high medical potency and traditionally it is used for cold treatment, typhoid, diarrhea, anti-hypertension, disinfectant, etc. This study conducted antibacterial testing on some common species of worms, namely Lumbricus rubellus, Pheretima posthuma and Megascolex sp. The antibacterial potency testing was done on typhoid causing bacteria, namely Salmonella typhi, and compared to generic antibiotic used for typhoid treatment. The result showed a lower potency then Ampicillin (between 25-35%), but the worms extract had potential to be developed as antibacterial materials or chemical compound.